Gambaran Penyakit Neurodegeneratif: Huntington, Alzheimer, dan Parkinson: Sebuah Tinjauan - Karlina, Ina; Andriyani, Eka Fitri Siti; Pratiwi, Arini Dian; Prasasti, Filosofia Florista Tesla Aulia; Tunjung, Woro Anindito Sri; Rohmah, Zuliyati; Nuriliani, Ardaning (Fakultas Kedokteran Universitas Trisakti, 2024)
Neurodegenerative diseases occur due to dysfunction of the nervous system, which is accompanied by memory and movement disorders. Neurodegenerative diseases can be viewed from an etiological and pathological perspective (pathophysiological and histopathological). The most common neurodegenerative diseases are Huntington's, Alzheimer's, and Parkinson's. This review article will review the etiology and pathology of Huntington's, Alzheimer's, and Parkinson's diseases. The method used in this writing uses journals and books from Google Scholar, PubMed, ResearchGate, and the Web. The keywords used are etiology, pathology, pathophysiology, histopathology, neurodegenerative disease, Huntington's, Alzheimer's, and Parkinson's. The author limited the last 10 years of literature used. Based on a literature review, it is known that the etiology of Huntington's disease is caused by mutations in the huntingtin gene on chromosome four. The pathology of Huntington's disease is caused by unstable expansion of trinucleotide-encoded polyglutamine (CAG) repeats. One of the histopathological features of Huntington's disease can be identified from increased iron levels in the striata of the brain. The etiology of Alzheimer's disease involves interactions between genetic factors, lifestyle, environment, and the aging process. The pathology of Alzheimer's disease occurs due to the presence of apolipoprotein and its relationship to 3 mutated genes. The histopathology of Alzheimer's disease is identified by the presence of neuronal cell death, which is characterized by the shrinking of the nuclei of brain neuronal cells and the cytoplasm has a more eosinophilic color. The etiology of Parkinson's disease is progressive nerve damage to certain areas of the brain. The pathophysiology of Parkinson's disease is thought to involve a reduction in striatal dopamine, which causes an increase in inhibitory output from the globus pallidus pars interna/substantia nigra pars reticulata (Gpi/SNr), resulting in movement suppression. Histopathologically, Parkinson's disease is characterized by degeneration of neurons and neurophagia. This review concludes that Huntington's, Alzheimer's, and Parkinson's diseases can be caused by aging and genetic factors. The pathology of the disease is due to mutations, increased levels of iron, apolipoprotein, neuronal cell death, increased inhibitory output, and neuronal degeneration. The symptoms caused can be motoric, cognitive, and psychiatric.